The Influence Of Authocratic Leadership Style And Organizational Culture On Turnover Intention Of Pt. Guna Mitra Prima Banjaran Employees (Case Study On Employees Of Pt. Guna Mitra Prima Banjaran) - Ependi, Maolana; Nurani, Nina (UNIVERSITAS PAKUAN, 2025)
This study aims to determine the effect partially and simultaneously with the research title The Effect of Authocratic Leadership Style and Organisational Culture on Turnover Intention in Employees at PT Guna Mitra Prima. This research uses a quantitative approach with survey methods and questionnaires as data collection instruments. The sampling technique used random sampling technique with the slovin formula consisting of 100 respondents. Data analysis was carried out using simple and multiple regression techniques to assess the effect of independent variables on the dependent. The results showed that partially Authocratic Leadership Style, and Organisational Culture have a significant influence on Turnover Intention. The results of this study provide implications from the Authocratic Leadership Style, and Organisational Culture on Turnover Intention, by applying a leadership style that is more suitable for PT Guna Mitra Prima's business such as a democratic leadership style for the sustainability of the company for the better, a fair organisational culture in giving awards and good communication to employees will certainly make added value in improving optimal results. Strengthening team collaboration and increasing adaptation to employees will contribute directly.